Apoptosis in follicles of individuals with female pattern hair loss is associated with perifollicular microinflammation - Ramos, P. M. [UNESP]; Brianezi, G. [UNESP]; Martins, A. C.P. [UNESP]; da Silva, M. G. [UNESP]; Marques, M. E.A. [UNESP]; Miot, H. A. [UNESP] (Wiley, 2016)
Objective: The objective of this study is to evaluate apoptosis in hair follicles of patients with female pattern hair loss (FPHL) and its association with follicular microinflammation. Method: Cross-sectional study involving 17 women with FPHL and five controls. Scalp skin samples were processed for HE and TUNEL assays. The variables were compared according to the categories of follicles (terminal versus miniaturized) and groups of patients (FPHL vs. controls). Results: There was a higher apoptosis index among miniaturized follicles and among the test cases (P < 0.01). Microinflammation was prominent among miniaturized follicles, especially from FPHL (P = 0.02). In addition, a positive correlation between inflammatory infiltrate and apoptosis in miniaturized follicles (rS = 0.68; P < 0.01) was found. Conclusions: Apoptosis was prominent in hair follicles from the FPHL group, as well as in miniaturized ones. Moreover, it was also correlated with the inflammatory infiltrate, which suggests that inflammation can lead to apoptosis and play a role in the pathogenesis of follicle miniaturization.
Keywords: alopecia; androgenic alopecia; apoptosis; hair growth; inflammation